Septage Management Pilots and Capacity Building in Indonesia : Synthesis Report - World Bank Group (World Bank, Washington, DC, 2016)
This report is a synthesis of the technical assistance (TA) and recommendations, carried out by the World Bank water and sanitation program (WSP) since September 2014. To achieve the target of 100 percent improved sanitation, there is a national drive to improve fecal sludge management (FSM). This TA recognizes that to achieve the goals it is necessary to support the development of national FSM policies, regulations, and guidelines, while also improving capacity at the local level by supporting the implementation of improved FSM models in target cities. The objective of the TA was to provide government with tested advice on how to scale up improved septage management nationwide through: (i) improvement of septage management in three cities through the application of new management models (local level); and (ii) assistance to national government in training and capacity building and the formulation of policies and regulations to improve septage management at scale (national level). This report is structured as follows: chapter one is the executive summary; chapter two gives the background to sanitation in Indonesia and to fecal sludge management in particular; chapter three provides an overview of the TA approach; chapter four gives details of the implementation of the TA; chapter five summarizes the lessons learned; and chapter six outlines the recommendations and next steps.